The Addressee Types of the Internet Open Letters; Procedia - Social and Behavioral Sciences; Vol. 206 : Linguistic and Cultural Studies: Traditions and Innovations, LKTI - Chesnokova I. A. Irina Anatolievna (2015, 2015)
Title screen